High potential inland valley maps for rice intensification in Cote d'Ivoire and Ghana - CGIAR Research Program on Rice (2020)
Inland valley mapping and their suitability for rice-based systems for two countries (Cote d'Ivoire and Ghana) has been completed and the outputs will be published soon.